Randomized placebo-controlled double-blind phase II study of zaltoprofen for patients with diffuse-type and unresectable localized tenosynovial giant cell tumors: The REALIZE study - Takeuchi, Akihiko; Endo, Makoto; Kawai, Akira; Nishida, Yoshihiro; Terauchi, Ryu; Matsumine, Akihiko; Aiba, Hisaki; Nakamura, Tomoki; Tandai, Susumu; Ozaki, Toshifumi; Hoshi, Manabu; Kayano, Daiki; et al. (Frontiers in Oncology, 2022)
Background: A tenosynovial giant cell tumor (TGCT) is a locally aggressive benign neoplasm arising from intra- or extra-articular tissue, categorized as localized (L-TGCT, solitary lesion) and diffuse (D-TGCT, multiple lesions) TGCT. Surgical excision is the mainstay of the treatment, and a high local recurrence rate of approximately 50% has been reported. We focused on zaltoprofen, a nonsteroidal anti-inflammatory drug that can activate peroxisome proliferator-activated receptor gamma (PPARγ) and inhibit the proliferation of TGCT stromal cells. Therefore, we conducted a randomized trial to evaluate the safety and effectiveness of zaltoprofen in patients with D-TGCTs or unresectable L-TGCTs. Methods: This randomized, placebo-controlled, double-blind, multicenter trial evaluated the safety and efficacy of zaltoprofen. In the treatment group, zaltoprofen (480 mg/day) was administered for 48 weeks; the placebo group received similar dosages without zaltoprofen. The primary outcome was progression-free rate (PFR) 48 weeks after treatment administration. Disease progression was defined as the following conditions requiring surgical intervention: 1) repetitive joint swelling due to hemorrhage; 2) joint range of motion limitation, 3) invasion of the adjacent cartilage or bone, 4) severe joint space narrowing, and 5) increased tumor size (target lesion). Results: Forty-one patients were allocated to the zaltoprofen (n=21) or placebo (n=20) groups. The PFR was not significant between the zaltoprofen group and the placebo group at 48 weeks (84.0% and 90.0%, respectively; p=0.619). The mean Musculoskeletal Tumor Society score significantly improved from baseline to week 48 in the zaltoprofen group (83.8% versus 93.0%, p=0.02), whereas that in the placebo group did not significantly improve (82.2% and 86.8%, respectively; p=0.167). One severe adverse event (grade 3 hypertension) was observed in the zaltoprofen group. Discussion: This is the first study to evaluate the efficacy and safety of zaltoprofen in patients with TGCT. No significant differences in PFR were observed between the groups at 48 weeks. Physical function significantly improved after zaltoprofen treatment. The safety profile of zaltoprofen was acceptable. This less invasive and safer treatment with zaltoprofen, compared to surgical removal, could be justified as a novel approach to treating TGCT. Further analysis of long-term administration of zaltoprofen should be considered in future studies.